2002
DOI: 10.1007/s00464-001-9052-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a moderate dose of alcohol on simulated laparoscopic surgical performance

Abstract: Simulated surgical performance is impaired severely when estimated blood alcohol concentration (BAC) is just above the UK legal limit for driving. These results contribute new, objective and quantitative evidence to the current debate about the use and misuse of alcohol within the medical profession.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 14 publications
(22 reference statements)
3
14
0
1
Order By: Relevance
“…Three further studies using lower doses of alcohol found no effect on surgical skills, managerial tasks or repeated tasks (boredom possibly having a detrimental effect on performance) (31,32,33).…”
Section: No Evidence For Impairment?mentioning
confidence: 95%
“…Three further studies using lower doses of alcohol found no effect on surgical skills, managerial tasks or repeated tasks (boredom possibly having a detrimental effect on performance) (31,32,33).…”
Section: No Evidence For Impairment?mentioning
confidence: 95%
“…Of the twentytwo studies that involved laparoscopic simulators and tested for construct validity, fifteen found the appropriate performance differences (e.g., attendings do better than residents and medical students) 9,10,15,17,[19][20][21][22][23][24][25][26][27][28][29] . Several studies examining the validity of the simulation experiences have been conducted, primarily with use of the guidelines outlined earlier.…”
Section: Simulation-based Education For Laparoscopy and Endoscopymentioning
confidence: 99%
“…There also have been studies showing there is no effect. Dorafshar et al [21] reported that surgical performance was impaired immediately after moderate alcohol consumption but this impairment was not observed the morning after.…”
Section: Caffeinementioning
confidence: 99%